Synthesis of ZnO nanoparticles mediated by natural products of Acanthus sennii leaf extract for electrochemical sensing and photocatalytic applications: a comparative study of volume ratios - Bekele, Eneyew Tilahun; Sintayehu, Yilkal Dessie; Murthy, H. C. Ananda; Shume, Minale Shegaw; Ayanie, Gezahegn Tadesse; Turunesh, Debela Jufar; R., Balachandran; Tan, K. B.; Chan, Kah Yoong; Ghotekar, Suresh; C. R., Ravikumar (Springer, 2022)
Determination of various chemical nutrients present within food samples using green nano-modified carbon paste working electrode (GNM-CPWE) is a novel and cost-effective technique. In addition, wastewater treatment in the presence of high surface area green nanocatalysts attracts researchers worldwide. In the present study, zinc oxide nanoparticles (ZnO NPs) were synthesized by using Acanthus sennii leaf extract within three volume ratios as 2:3 (40 mL precursor: 60 mL extract), 1:1 (50 mL precursor: 50 mL extract), and 3:2 (60 mL precursor: 40 mL extract). Physicochemical characterization of ZnO NPs was confirmed using modern technical tools such as XRD, SEM–EDX, TEM, HR-TEM, SAED, UV-DRS, and FTIR methods. Comparative performance studies of ZnO NPs form within different volume ratios were investigated in sensing of ascorbic acid (AA) and degradation of acid orange 88 (AO88) dye. The average crystallite size was found to be 24.19, 19.55, and 23.07 nm for the 2:3, 1:1, and 3:2 ratios, respectively. SEM–EDX with TEM and HR-TEM-SAED depicts that ZnO NPs have spherical shape. UV-DRS proved that the 2:3, 1:1, and 3:2 have bandgap (Eg) energy of 3.28, 3.31, and 3.25 eV, respectively. FTIR analysis indicates the presence of various capping and reducing agents within leaf extract of Acanthus sennii. Electrochemical sensing potential of ZnO (1:1) modified CPWE toward AA was found to be more effective with a best detection limit of 0.200 mM as compared to the counterpart ratios. This might be due to its small D and enhanced catalytic property. The percent degradation efficiency of ZnO (1:1) toward AO88 dye was calculated to be 62.6%. The enhanced degradation potential of ZnO (1:1) might be attributed due to its optical property and relatively small D value as compared to the counterpart ratios.